Boosting activity, thermostability, and lifetime of iron ethylene polymerization catalysts through gem‐dimethyl substitution and incorporation of ortho‐cycloalkyl substituents. (14th July 2021) - Zhang, Randi; Han, Mingyang; Oleynik, Irina V.; Solan, Gregory A.; Oleynik, Ivan I.; Ma, Yanping; Liang, Tongling; Sun, Wen‐Hua
Abstract: Six types of ferrous chloride complex, [2‐(ArN=CMe)‐8‐(ArN)‐7, 7‐Me2 C9 H6 N]FeCl2 (Ar=2‐(C5 H9 )‐6‐MeC6 H3 Fe1, 2‐(C6 H11 )‐6‐MeC6 H3 Fe2, 2‐(C8 H15 )‐6‐MeC6 H3 Fe3, 2‐(C5 H9 )‐4, 6‐Me2 C6 H2 Fe4, 2‐(C6 H11 )‐4, 6‐Me2 C6 H2 Fe5, 2‐(C8 H15 )‐4, 6‐Me2 C6 H2 Fe6 ), each bearing a gem ‐dimethyl‐substituted N, N, N ‐chelating ligand that differs in the ortho ‐cycloalkyl ring size and para ‐substituent of the N ‐aryl groups, are disclosed. All complexes have been prepared by a straightforward one‐flask route and characterized by FT‐IR spectroscopy and elemental analysis. In the case of Fe1, oxidation to form the oxo‐bridged diferric species [2‐(2‐(C5 H9 )‐6‐MeC6 H3 N=CMe)‐8‐(2‐(C5 H9 )‐6‐MeC6 H3 N)‐7, 7‐Me2 C9 H6 N]FeCl(μ‐O)FeCl3 (Fe1' ) has been demonstrated and its structural identity confirmed by single crystal X‐ray diffraction. Following treatment with either methylaluminoxane (MAO) or modified methylaluminoxane (MMAO), Fe1 –Fe6 exhibited optimal catalytic activities at 60°C for ethylene polymerization [up to 2.35 × 10 7  g of PE (mol of Fe) −1  h −1 for Fe1 /MMAO] producing linear polyethylene; even over prolonged run times, high activities were maintained. Moreover, this family of iron catalysts exhibited remarkable thermostability by displaying appreciable activity at temperatures as high as 100°C [activity up to 7.8 × 10 6  g of PE (mol of Fe) −1  h −1 ]. By varying the ring size of the ortho ‐cycloalkyl and para ‐ R 2 group ( R 2  = H, Me), excellent control over molecular weight of the polyethylenes could be achieved with values in the range 1.4–67.8 kg mol −1 obtainable. In addition, end‐group analysis of the polymers generated with Fe /MAO or Fe /MMAO revealed that both β ‐H elimination and chain transfer to aluminum are competitive processes during chain termination. Abstract : Targeted ligand design has allowed access to iron catalysts that not only display high activity, appreciable catalytic lifetime and good thermal stability and but also afford linear polyethylenes displaying a wide range in molecular weights.